1964
DOI: 10.1136/jnnp.27.4.351
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and electrophysiological study of the pattern of conduction times in the distribution of the sciatic nerve

Abstract: This study defines the normal range of motor conduction velocities and distal latencies in nerves to various leg and foot muscles, and in the proximal and distal segments of the same nerve to the foot muscles. The significance of differences in temperature in individual variations in nerve conduction velocity has been evaluated.A series of patients with various diseases of the sciatic nerve or its branches has been similarly investigated. The pattern of abnormality in nerve conduction has been found to be of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
32
0

Year Published

1966
1966
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 12 publications
8
32
0
Order By: Relevance
“…The rate of motor conduction in fibres of the radial nerve between axilla and elbow was similar to the velocities in the nerve between the supraclavicular fossa and elbow (Gassel and Diamantopoulos, 1964;Tbnnis, 1965 and elbow than between elbow and forearm (Jebsen, 1966b). A similar difference between conduction rates in proximal and distal segments of the median, ulnar, and sciatic nerves has been described (Gassel and Trojaborg, 1964;Trojaborg, 1964).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The rate of motor conduction in fibres of the radial nerve between axilla and elbow was similar to the velocities in the nerve between the supraclavicular fossa and elbow (Gassel and Diamantopoulos, 1964;Tbnnis, 1965 and elbow than between elbow and forearm (Jebsen, 1966b). A similar difference between conduction rates in proximal and distal segments of the median, ulnar, and sciatic nerves has been described (Gassel and Trojaborg, 1964;Trojaborg, 1964).…”
Section: Discussionmentioning
confidence: 56%
“…The conduction time was measured from the stimulus to the onset of the action potential; the amplitude was measured peak-to-peak. The distance between the cathode at axilla and at elbow was measured with obstetric calipers (Gassel and Diamantopoulos, 1964).…”
Section: Methodsmentioning
confidence: 99%
“…The distal slowing of conduction velocity was about equally marked for fast and slow nerve fibres. A distal slowing of conduction velocity within limbs has previously been found in man, and such studies have indicated that factors other than temperature would be responsible for much of the phenomenon (Gassel & Trojaborg, 1964;Mawdsley & Mayer, 1965;Mavor & Atcheson, 1966).…”
Section: Resultsmentioning
confidence: 99%
“…For studies involving measurements of axonal conduction velocity it is of interest to know if the conduction speed may change along the peripheral courses of single nerve fibres. Previous studies on man have indicated that, within a limb, conduction velocity becomes progressively slower in the more distal portions of a given nerve (Gassel & Trojaborg, 1964;Trojaborg, 1964;Mawdsley & Mayer, 1965;Mavor & Atcheson, 1966). During intracellular studies on forelimb motoneurones in the baboon we discovered that, at least in this animal, there is a marked slowing of conduction velocity in the most proximal portion of single nerve fibres; the conduction velocity was found to be slower within the brachial plexus (between spinal cord and shoulder) than within the arm.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12]17,[19][20][21] These factors are based on values obtained from normal nerves in normal individuals and may well not be applicable to diseased nerves in the clinical situation. 2,3,5,6,8,11,13,[15][16][17][18]23,25 The aim of this study was to determine the appropriateness of using temperature correction factors in carpal tunnel syndrome (CTS) and to assess the effect of temperature on various nerve conduction parameters in diseased median and normal ulnar nerves. …”
mentioning
confidence: 99%